Levee as a flood mitigation option in Malaysia, its' susceptibility to failure and design approach - Mohd Nordin, N.F. (Penerbit UTHM, 2019)
Flooding is a major concern globally affecting many countries around the world, including Malaysia. As Earth undergo global climate change, intensified flood events are also expected to increase. One of the available structural flood mitigation measures is the implementation of levees. Effective and economical in preventing floods, levees can also be integrated into urban landscaping works and consequently improve the aesthetic appeal of the river frontage. However, levees also pose a critical risk as it can be catastrophic if any stretch of the levee structure fails. This paper summarizes the type of levee failures that can occur and discusses the basic design checks required thus providing levee designers an overview of the risks that needs to be addressed to ensure adequate levee design. Â© Universiti Tun Hussein Onn Malaysia Publisher's Office.